2011
DOI: 10.1051/0004-6361/201117470
|View full text |Cite
|
Sign up to set email alerts
|

SDO AIA and Hinode EIS observations of “warm” loops

Abstract: We present simultaneous observations of active region "warm" (1 MK) loops using the Solar Dynamics Observatory (SDO) Atmospheric Imaging Assembly (AIA) and Hinode EUV Imaging Spectrometer (EIS). Sample EIS spectra for a loop footpoint and a lop leg region are presented, and are used to describe the spectral lines which contribute to the six AIA EUV channels, both directly and predicted with DEM modeling. We find good overall agreement between observed and predicted count rates for the 131 Å, 193 Å, and 335 Å b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
106
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 24 publications
8
106
0
Order By: Relevance
“…These SDO/AIA observations provide unprecedented coverage in terms of spatial and temporal resolutions, and can provide new diagnostic applications, once the atomic data are well understood. As shown in O'Dwyer et al (2010) andDel Zanna et al (2011), these bands are dominated by Fe x and Fe viii in normal quiet Sun conditions. However, several unidentified spectral lines have been observed in the AIA passbands with high-resolution grazing incidence solar spectrometers (cf.…”
Section: Introductionmentioning
confidence: 82%
“…These SDO/AIA observations provide unprecedented coverage in terms of spatial and temporal resolutions, and can provide new diagnostic applications, once the atomic data are well understood. As shown in O'Dwyer et al (2010) andDel Zanna et al (2011), these bands are dominated by Fe x and Fe viii in normal quiet Sun conditions. However, several unidentified spectral lines have been observed in the AIA passbands with high-resolution grazing incidence solar spectrometers (cf.…”
Section: Introductionmentioning
confidence: 82%
“…Several authors Young et al 2012;Del Zanna et al 2011) have raised the question of which coronal imaging channel best represents the coronal structures that display plasma upflows in the EIS Fe xii lines. The reason for this is the contribution of a wide range of spectral lines to the wavelength range covered by the AIA 171 Å and 193 Å, and TRACE 171 Å channels.…”
Section: Aiamentioning
confidence: 99%
“…The channel also has a contribution from Fe x. The AIA 193 Å channel is dominated by three Fe xii lines, but it also has a significant contribution from the transition region from unidentified lines (Del Zanna et al 2011).…”
Section: Aiamentioning
confidence: 99%
“…3 above, emission from transition region plasma will dominate in all of AIA's EUV channels during a flare's precursors and early impulsive rise, while emission from plasma at temperatures around 10 MK will dominate later during the event. In an even more recent comparison of AIA images of a non-flaring loop footpoint and leg with coordinated EUV spectra from Hinode's Extreme-ultraviolet Imaging Spectrometer (EIS, Culhane et al 2007), Del Zanna et al (2011) showed that emission from lines formed at transition region temperatures can be significant for all of AIA's EUV channels, and dominant in some cases. Their observation of numerous unidentified lines in the EIS spectra underscored the need for further work on the relevant atomic data before AIA images can be reliably used for plasma diagnostic purposes.…”
Section: Based On Aia and Cdsmentioning
confidence: 99%